Testing and initial verification of the world's first metal 3D printed bridge - Gardner, Leroy; Kyvelou, Pinelopi; Herbert, Gordon; Buchanan, Craig (Journal of constructional steel research, 2020)
Wire and arc additive manufacturing (WAAM) is a method of metal 3D printing that is suited to the requirements of the construction industry in terms of scale, speed and cost. Using this technology, a 10.5 m span footbridge, the first of its kind, has been printed. The testing, analysis and initial verification of the bridge and its components are described herein. The experiments performed included advanced geometric analysis, material testing, compressive testing of cross-sections and full-scale load testing of the bridge at various stages throughout and post construction. Parallel finite element modelling of the full bridge and its constituent elements has also been performed as part of the verification. Confirmation that the bridge was able to sustain its full serviceability design load enabled to the bridge to be unveiled to the public, with controlled access, for Dutch Design Week 2018. Further testing under ultimate limit state design loading is planned before the bridge is placed in its final location and fully opened to the public. The project highlights the potential for metal 3D printing in structural engineering, as well as the necessary considerations for design. [Display omitted] •Initial verification of the world's first metal 3D printed bridge is undertaken.•Material behaviour of the bridge is determined by tensile coupon testing.•Compressive structural response of the key bridge components is assessed by stub column testing.•Full-scale structural load testing of the bridge both during and after construction under different load cases is described.•Finite element simulations of the bridge are carried out and comparisons are made with the test results.